ANALISIS NILAI-NILAI PENDIDIKAN DALAM NOVEL SEPATU DAHLAN KARYA KHRISNA PABICHARA - Susanti, Nila; Bahardur, Iswadi; Yusandra, Titiek Fujita (Pendidikan Bahasa Indonesia, 2013)
The research almed to describe educated values in novel entitled Sepatu Dahlan written by Khrisna Pabichara. Kinds of this research was used describtive methods. The results of this research are: firstly, the educated values related with hard work that both father and mother who have hard work spirit to fullfil then children needs, itâs same with Dahlan who hard work spirit up to reach his goâal and his dream one self. Second, educated values related with caring that love and care wich. Dahlan father, mother, and Zain has in this novel is well and become into harmony is family. Third, the educated values related with disciplin that disciplin wich always implemented by the father to conduct his children not to waste the time. Fourth, educated values related with patience wich had by Dahlan, father, mother, to face their poverty condition. Fifth, educated values related with responsible that father taught his children to be a responsible one. The lesson was always implemented by Dahlan in everything he did.